2000
DOI: 10.1038/sj.gt.3301056
|View full text |Cite
|
Sign up to set email alerts
|

Cell delivery, intracellular trafficking and expression of an integrin-mediated gene transfer vector in tracheal epithelial cells

Abstract: The mechanism of cell entry and intracellular fate of a gene transfer vector composed of a receptor-targeting, DNA-condensing peptide, RGD-oligolysine, a luciferase encoding plasmid DNA (pDNA) and a cationic liposome was examined. We demonstrate by confocal microscopy, electron microscopy and subcellular fractionation that the major mechanism of entry of the vector is endocytic. The vector complex rapidly (5 min) internalizes into early endosomes, then late endosomes and lysosomes. Entry involves, at least in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 45 publications
5
74
0
Order By: Relevance
“…19 In contrast, here, we observed that both the plasmid DNA and the glycosylated polylysines were present in the nucleus after 2 h and up to 18 h. In addition, at 8 h and depending on the sugar moiety linked to the polylysine, complexes were seen in the nucleus of 27-42% of the cells. These results are in agreement with previous studies showing that plasmid DNA complexed to cationic polymers, such as polyethylenimine 20 or polylysine 13,21,22 were present in the nucleus. The kinetics of entry into the nucleus were quite similar to those reported previously: 20,22 plasmid DNA was detected in the nucleus between 1 and 6 h and its nuclear accumulation was time-dependent.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…19 In contrast, here, we observed that both the plasmid DNA and the glycosylated polylysines were present in the nucleus after 2 h and up to 18 h. In addition, at 8 h and depending on the sugar moiety linked to the polylysine, complexes were seen in the nucleus of 27-42% of the cells. These results are in agreement with previous studies showing that plasmid DNA complexed to cationic polymers, such as polyethylenimine 20 or polylysine 13,21,22 were present in the nucleus. The kinetics of entry into the nucleus were quite similar to those reported previously: 20,22 plasmid DNA was detected in the nucleus between 1 and 6 h and its nuclear accumulation was time-dependent.…”
Section: Discussionsupporting
confidence: 93%
“…3,[11][12][13] Indeed, such a mechanism is likely at work for glycosylated polylysines. Our previous findings 7 and those reported herein suggest such a mechanism: a mannose-specific membrane lectin is strongly expressed at the surface of ΣCFTE29oϪ cells and mannosylated complexes are the glycosylated complexes most efficiently incorporated into the cells, as shown by flow cytometry 7 and confocal microscopy (this study).…”
Section: Discussionmentioning
confidence: 99%
“…100 An Arg-Gly-Asp (RGD) targeted vector appeared to enter into clathrin-coated pits and vesicles, as visualized by EM, and uptake was inhibited by K + depletion. Uptake was also inhibited with hypertonic medium, which renders clathrin unavailable for assembly.…”
Section: Targeted Lipopolyplexes a Ligand Which Normallymentioning
confidence: 99%
“…Two elements are necessary to efficiently express foreign genes in cells: passage of DNA across the cell membrane and transport into the nucleus (Colin et al, 2000). From this point of view, recombinant viral vectors have a great advantage by depending on their intrinsic machinery for infection.…”
mentioning
confidence: 99%